2014
DOI: 10.4028/www.scientific.net/ssp.219.170
|View full text |Cite
|
Sign up to set email alerts
|

Detection of HO<sub>2</sub>•/O<sub>2</sub>•<sup>-</sup> Radicals Formed in Aqueous Solutions Irradiated with Megasonic Waves Using a Cavitation Threshold (CT) Cell Set-Up

Abstract: Acoustic cavitation, especially transient cavitation, in solutions is accompanied by a number of physical and chemical effects. Due to high temperature and pressure conditions inside bubbles at their collapse, excitation of various species as well as formation of radicals occurs in solution [1-4]. Water molecules excited by megasonic irradiation typically dissociate to hydrogen and hydroxyl radicals (H• and OH•) [5]. The hydroxyl radical is a strong oxidant while the hydrogen radical has reducing properties. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Sonochemical reactions produce active free radical species such as OH• (hydroxyl), HO2• (hydroperoxyl) and H• (hydrogen). Hydrogen radicals have reducing properties, and in fact, can react with oxygen to form hydroperoxyl (HO2•) radicals that can act both as a reducing and weak oxidizing agent [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sonochemical reactions produce active free radical species such as OH• (hydroxyl), HO2• (hydroperoxyl) and H• (hydrogen). Hydrogen radicals have reducing properties, and in fact, can react with oxygen to form hydroperoxyl (HO2•) radicals that can act both as a reducing and weak oxidizing agent [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…While many studies on the characterization of hydroxyl and hydroperoxyl radicals have been reported [5][6][7], the detection and quantitation of hydrogen radicals formed in aqueous solution during sonication have not received much attention. In the detection of HO2• and H• radicals, their reaction with cupric (Cu 2+ ) ions has been recognized.…”
Section: Introductionmentioning
confidence: 99%